Biodegradable copolypeptide hydrogel prodrug accelerates dermal wound regeneration by enhanced angiogenesis and epithelialization. Issue 19 (16th March 2018) - Chen, Anqi; He, Huacheng; Ma, Guanglong; Li, Yi; Jiang, Shishuang; Xuan, Xuan; Song, Yi; Zhang, Cuiyun; Xiao, Jian; Xu, Yunsheng; Wu, Jiang; Chen, Shengfu
Abstract : Biodegradable hydrogel as a wound dressing and therapeutic prodrug promoting wound regeneration through enhanced angiogenesis and epithelialization. Abstract : Hydrogels are one of the most promising wound dressings. However, their effectiveness on wound healing is still largely limited due to either the non-degradability or the release of non-therapeutic degradable products. Herein, a biodegradable copolypeptide hydrogel based on the glutamic acid and lysine was synthesized and applied as both wound dressing and therapeutic prodrug. The hydrogel can degrade in the existence of elevated degradative enzymes in a wound environment, which will release therapeutic amino acids to enhance the wound healing. In vivo results found that the hydrogel could effectively promote wound regeneration in both macroscopic and microscopic scales. Further investigation revealed that the wound healing effect of the hydrogel was highly attributed to its enhanced impact on angiogenesis, cell proliferation and re-epithelialization of the wound. All in all, the present study proves that the degradable copolypeptide hydrogel can efficiently improve wound healing and indicates its potent clinical application for wound regeneration.